Drug shortages in low- and middle-income countries: Colombia as a case study - Martha L. Sabogal De La Pava; Emily L. Tucker (Taylor & Francis Group, 2022)
Background Drug shortages are a global problem. Analyzing shortages worldwide is important to identify possible relationships between drug shortages across countries, determine strategies that reduce drug shortages, and reduce the inequality in access to medicines between countries. In contrast to well-documented shortages in high-income countries, there are few studies that consider low- and middle-income economies. We evaluate drug shortages in one middle-income country, Colombia. Methods We collected data from INVIMA, the institution responsible for managing medicine shortage alerts in Colombia. We classified the data using the Anatomical Therapeutic Chemical (ATC) classification system and analyzed them using descriptive statistics. We considered a study period from 2015 to 2021 (vital medicines) and from 2010 to 2020 (non-vital medicines). Results In total, 173 unique ATC codes were in shortage. These included antidotes, alimentary tract and metabolism products, anesthetics, cardiac stimulants and antithrombotic agents. The major causes were manufacturing problems and few suppliers. Drug shortages substantially increased from 2020 to May 2021 due to the COVID-19 pandemic. Among resolved shortages, the average duration was 1.6 years with a standard deviation of 1.9 years. The longest, naloxone tablets, were in shortage for almost 10 years. Conclusions Drug shortages are a persistent problem in Colombia. Government institutions have made progress in implementing systems and procedures to report them. However, the approaches implemented need to be maintained and refined. This study lays the groundwork for the analysis of drug shortages in other LMICs. We highlight the necessity of addressing drug shortages in their global context and reducing the inequality in access to medicines between countries.